The Investigation Impact In Rubber Wastewater Invitalized of Land Surface For Rubber Processor Industry at PT. Bukit Angkasa Makmur Bengkulu - Bursamin Bursamin; Lina Widawati; Diah Azhari; Yudian Syahputra; Budi Prastia (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose : This research aims to provide a scientific basis for controlling environmental pollution due to rubber processing industry activities and to support more environmentally sound industrial practices. Methodology: The research method used is a quantitative method with a descriptive-analytical approach including soil sampling carried out at two locations, namely points affected by waste seepage and control points (not affected) as a comparison. Soil samples are then analyzed in the laboratory to measure physico-chemical parameters including pH, Chemical Oxygen Demand (COD), nitrogen content and soil texture. Results: The results of the investigation into the impact of rubber waste infiltration show that the infiltration of untreated rubber industry liquid waste at PT. Bukit Angkasa Makmur (BAM), Bengkulu, triggers a decline in water and soil quality. This is characterized by a spike in BOD parameters (93–9343mg/L), COD, and TSS. This condition causes damage to the ecosystem and threatens the availability of clean water for local residents. Conclusion: Investigation of the impact of rubber waste infiltration shows that inadequately treated rubber industrial wastewater infiltration results in serious environmental damage, such as groundwater pollution, decreased fertility, and the formation of anaerobic conditions due to high concentrations of BOD (93-9,343 mg/L), COD, and TSS. The implementation of Waste Water Treatment Plants (IPAL) based on 3R (Reduce, Reuse, Recycle) is very urgent to minimize pollution and restore soil quality. Type of Paper : Research article.